O comportamento do adjetivo easy na perspectiva da teoria do léxico gerativo: um olhar semântico - Rodrigues, Sergiane David (2019)
The English language is still considered one of the most widely spoken languages in the world, even with a variety of other languages. In Brazil, scholars discussed a lot about the teaching of this language, studies based on several areas of the linguistic field. We decided to look at this language through the lens of Semantics and, for this, this research has as general objective to analyze the semantics of the adjective easy as an integral part of a sentence searching, in this way, the understanding of the diverse semantic behavior that this adjective can assume when accompanied by a name. As specific objectives, the research aims to verify the semantic behavior that easy affords when it is appointed in different contexts; investigate the influence it exerts on the name that follows it and identify the characteristic behavior of the adverbs that possibly easy assumes. To achieve these objectives, we prioritize real language data, and part of a data clipping taken from the British National Corpus, an online corpus. From this corpus, we selected 54 sentences that were divided into three categories, according to the variations of semantic behavior identified in easy, in order to verify the possible regularities of meaning of this adjective in the English language. Such categories are: category I, easy assumes semantic behavior of adverb with the name that accompanies it; category II, easy takes on another meaning attributed by the complement and category III, the meaning of easy is partially hidden in the sentence. As a theoretical contribution to the analysis, the research is based on the considerations about the creativity of the meaning of words, the studies on the semantics of adjectives and polysemy, found in the Theory of Generative Lexicon - TLG, developed by James Pustejovsky (1995). We also present considerations of other authors such as Hovav and Levin (2005), Ferrarezi Junior and Basso (2013), Moura (2000, 2001), Chishman (2000), Ullman (1964), Jezek (2017), Ferraz ; 2013; 2014) and Aragão Neto (2004; 2012). This research is characterized as qualitative and has a descriptive-interpretative approach. The results obtained in the analyzes of the three categories selected reveal that the adjective easy can assume predominantly the characteristic behavior of the adverbs, in addition to other forms of identified meanings that are apparently less frequent.